PATTERN OF ANTIHYPERTENSION DRUG ADMINISTRATION IN HYPERTENSION PATIENTS IN OUTPATIENT TUAN RONDA HOSPITAL PEMATANG RAYA, SIMALUNGUN DISTRICT - Nurmala (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2022)
Until now, hypertension is still a big challenge in Indonesia. In accordance with the 2013 Riskesdas data, the prevalence of hypertension is quite high, namely 25,896. This study aims to determine the pattern of administration of antihypertensive drugs to hypertensive patients at Tuan Rondahaim Hospital, Pematang Raya, Simalungun Regency. This research was conducted using a descriptive research design and data collected retrospectively. The material used is data from hypertension patient prescriptions at Tuan Rondahaim Hospital, Pematang Raya, Simalungun Regency. The number of samples used was obtained as many as 231 patients. The results obtained were that hypertension patients based on sex characteristics were mostly women 54.1196, the most age was 61 — 80 years 65.806. On the profile of antihypertensive drug use by patients, There are 5 classes of antihypertensives used. The most widely used anti-pertensive class Blocker (CCB) was the Calcium Channel amlodipine group of 61.03%, which was used by 141 patients, then the diuretic class of furosemide type was 41.9% used by 97 patients.